Muhammadiyah And Islamic Education Reform - Utami, Yeri; Tri, Yunanto Andang (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2025)
: Muhammadiyah is an Islamic organization founded by K.H. Ahmad Dahlan in 1912 in Yogyakarta and has become one of the largest Islamic organizations in Indonesia that has an important role in Islamic education reform. Muhammadiyah integrates Islamic values with modern science to create a generation that is intellectually and morally competent. To date, Muhammadiyah has managed more than 10,000 educational institutions, ranging from early childhood education to universities spread throughout Indonesia. Talking about Muhammadiyah education is certainly inseparable from the discussion of Muhammadiyah's educational philosophy which emphasizes the integration between religious and general knowledge, rejecting the dichotomy of